2013
DOI: 10.3389/fpsyg.2013.00285
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Systems Account of Sensorimotor Contingencies

Abstract: According to the sensorimotor approach, perception is a form of embodied know-how, constituted by lawful regularities in the sensorimotor flow or in sensorimotor contingencies (SMCs) in an active and situated agent. Despite the attention that this approach has attracted, there have been few attempts to define its core concepts formally. In this paper, we examine the idea of SMCs and argue that its use involves notions that need to be distinguished. We introduce four distinct kinds of SMCs, which we define oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 57 publications
1
96
0
1
Order By: Relevance
“…While some have begun to flesh out the implementational details of sensorimotor perception by appealing to entirely non-representational dynamical systems (e.g. Buhrmann et al 2013;Flament-Fultot 2016), others have developed the approach in a more cognitivist framework, for example Seth (2014), who has combined it with a predictive processing account, or Maye and Engel (e.g. 2016) who have 1 3 used a representational implementation of sensorimotor knowledge in robot control architectures.…”
Section: Sensorimotor Enactivismmentioning
confidence: 99%
“…While some have begun to flesh out the implementational details of sensorimotor perception by appealing to entirely non-representational dynamical systems (e.g. Buhrmann et al 2013;Flament-Fultot 2016), others have developed the approach in a more cognitivist framework, for example Seth (2014), who has combined it with a predictive processing account, or Maye and Engel (e.g. 2016) who have 1 3 used a representational implementation of sensorimotor knowledge in robot control architectures.…”
Section: Sensorimotor Enactivismmentioning
confidence: 99%
“…approaching dark corners), selecting others, actively seeking some, sequentially switching from one to another, etc. (see Buhrmann et al 2013). This bundle of habits is, partly, tied or meshed within the brain, where most of the reliable plasticity of habits and the capacity for selective enactment lies.…”
Section: Sensorimotor Autonomy Revisitedmentioning
confidence: 96%
“…E ? S. It is, however, worth noting that the set of possible sensorimotor correlations that a body can enact in a particular situated condition is the environment for the agent (Buhrmann et al 2013). It is only within this environment that certain neurodynamic patterns can be enacted, only when the sensorimotor environment is actively inhabited in this sense, when sensorimotor contingencies are enacted through sensorimotor coupling, that certain functionally distinct neurodynamic patterns emerge.…”
Section: Understanding the Sensorimotor Constitution Of Neurodynamic mentioning
confidence: 99%
See 1 more Smart Citation
“…The study is a prototypical case in which a supposedly complex cognitive ability is demonstrated in a very simplified system, which however preserves the relevant brainbody-environment interactions that pertain to biological systems (Beer, 2003). Following this study, a number of similar minimalistic approaches have been proposed to account for the emergence of cognition in artificial systems (Barandiaran, 2006;Dale and Husbands, 2010;Buhrmann et al, 2013;Iizuka et al, 2013). In few cases, a specific parallel with the target biological system has been proposed.…”
Section: Modelmentioning
confidence: 99%